Understanding How and Why Cities Engage with Climate Policy: An Analysis of Local Climate Action in Spain and Italy. - De Gregorio Hurtado, Sonia; Olazabal, Marta; Salvia, Monica; Pietrapertosa, Filomena; Olazabal, Eduardo; Geneletti, Davide; D’Alonzo, Valentina; Di Leo, Senatro; Reckien, Diana (TeMA - Journal of Land Use, Mobility and Environment, 2015)
Cities significantly contribute to climate change while at the same time have government capacity to efficiently act in the fields of mitigation and adaptation. Their climate capacity is being increasingly recognized by international institutions and has been pointed out as crucial in the multi-level government scenario of the European Union (EU). Addressing the challenges of climate change at urban level is a complex issue which requires a holistic approach to strategic urban planning. Understanding why and how cities start action can help to identify the barriers they face when addressing climate change, and how national governments, regions and international bodies can support local authorities in their climate fight. This work aims to contribute to the provision of knowledge necessary to have a better and deeper insight in urban climate action. The study investigates the state-of-art of urban climate plans in two countries, Spain and Italy, which share similarities on many levels (i.e. cultural, geographical, climate vulnerabilities, urban configurations and institutional framework). The research analyses 26 Spanish cities and 32 Italian cities included in the Eurostat Urban Audit (UA), focusing on the actions taken by big and medium municipalities in reducing their contribution to climate change and to become more resilient to changing weather patterns. The results of the analysis show a trend towards an increasing awareness on climate mitigation (highly focused on energy efficiency and the promotion of cleaner energy sources), while adaptation remains an incipient local policy area in both countries. The analysis identifies also the beneficial influence of national and international climate city networks.